SIMULASI/PEMODELAN DAMPAK IMPLEMENTASI PENEGAKAN KEBIJAKAN PENANGKAPAN IKAN TERUKUR MELALUI PENGAWASAN DAN PATROLI KAPAL PENANGKAP IKAN DENGAN PENDEKATAN SISTEM DINAMIK (STUDI KASUS : KAWASAN PERAIRAN LAUT KABUPATEN NATUNA) - Satar, Abdul
This study aims to determine the impact of implementing measurable fishing enforcement stipulated through Government Regulation No. 11 year 2023 concerning Measured Catching of Fish, the regulation regulates the imposition of sanctions for violations of provisions on fishing zones and fishing quotas, which are enforced through monitoring and patrolling of fishing vessels. This study uses dynamic system modeling by modeling the fishery resource system, fishing business system, and regional economic system in the marine waters of Natuna Regency. The behavior of the dynamic system model from 2022 to 2041 shows that in 2030 and beyond there will be overfishing in the marine waters of Natuna Regency because fishing exceeds the Allowed Catch Amount (JTB), which has been regulated in KepmenKP 19/2022. Increasing fishing catches will certainly increase the value of fisheries production which grows from IDR 2.48 trillion (2022) to IDR 30.14 trillion (2041), which contributes to significantly increasing the GRDP of Natuna Regency to IDR 507 trillion in 2041. However, fish theft is rife with estimated loss of IDR 487.3 billion/year. Therefore, the problem of overfishing and illegal fishing is handled by intervening in the policy of monitoring and patrolling fishing vessels with three scenarios, when the policy is running at 25%, 50% and 100%. With policy interventions that are fully operational, the level of fisheries utilization is controlled to decrease by 45.1% from the scenario without policies, so that overfishing does not occur. In addition, the value of fishery theft decreases by 70% from the base scenario. The application of fishing zoning regulations and fishing quotas through sanctions instruments will certainly reduce fisheries production and GRDP of Natuna Regency by 30% and 17%, respectively, but these policies are effective in protecting fisheries resource ecosystems and significantly reducing cases of fish theft.